A fuzzy failure mode and effects approach to analyse concentrated inspection campaigns on board ships - Akyüz, Emre; Akgun, Ilker; Celik, Metin (Routledge Journals, Taylor & Francis Ltd, 2016)
Maritime actions against substandard operations of ships are a great deal of memorandum of understanding (MoUs) under regional basis agreements among port state control (PSC) organisations. Herein, concentrated inspection campaigns (CIC), performed by the different members of MoUs in certain periods, are a monitoring strategy to effectively control the core operational matters encountered in fire-safety systems, propulsion and auxiliary machinery system, lifesaving appliances, working conditions on board ships, etc. This paper proposes a quantified maritime safety analysis based on fuzzy failure mode and effects analysis (FMEA) to evaluate CIC database of MoUs in order to achieve advance creative solutions. Demonstration studies are performed on the special database on fire-safety system deficiencies. Since the fuzzy FMEA outcomes point out the risk prioritisation numbers and relevant control options, the paper attempts to transform CIC feedback into useful information in terms of enhancing the ship PSC inspection concept (e-PSC inspection). The paper theoretically contributes to safety analysis methods in literature while demonstration of e-PSC inspections offers an insight into maritime industry in safety improvement.
Keywords: Maritime safety analysis; maritime regulation; risk assessment; port state controls; fire-safety system